Performance evaluation of plasma nitrided 316L stainless steel during long term high temperature sodium exposure - Akash Singh; R. Thirumurugesan; S. Krishnakumar; Revati Rani; S. Chandramouli; P. Parameswaran; R. Mythili (Nuclear Engineering and Technology, 2023)
Enhancement of wear resistance of components used in fast reactors is necessary for long service life of the components. Plasma nitriding is a promising surface modification technology to impart high hardness and improved wear resistance of various steel components. This study discusses the characterization of chrome nitrided SS316L casing ring used in secondary sodium pump of fast breeder reactor and its stability under long term sodium exposure. Microstructural and hardness analysis showed that stress relieved component could be chrome nitrided successfully to a thickness of about 100 μm. Assessment of in-sodium performance of the chrome nitrided casing ring subjected to long term exposure up to 5000h at 550°C, showed retention of chrome nitrided layer with a case depth almost similar to that before sodium exposure. A slight decrease in the hardness was observed due to prolonged high temperature sodium exposure. Tribological studies indicate very low coefficient of friction indicating the retention of good wear resistance of the coating even after long term sodium exposure.